2009
DOI: 10.1155/2009/808209
|View full text |Cite
|
Sign up to set email alerts
|

Potential Intensive Care unit Ventilator Demand/Capacity Mismatch due to Novel Swine‐Origin H1N1 in Canada

Abstract: Canada's health care system must be prepared for the possibility of a significant influx of ICU patients during the second wave of swine-origin H1N1. Efficient vaccination and other disease prevention measures can reduce the attack rate to manageable levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…An important "therapeutic gap" therefore exists, and novel drugs are needed to either delay the onset of ARDS or reduce its severity in this cohort of influenza-infected patients. Such drugs could reduce the potential for ICU overload in pandemic situations (29,30), maintaining the ability of the healthcare system to provide adequate care to all who require it (12,14).…”
Section: Discussionmentioning
confidence: 99%
“…An important "therapeutic gap" therefore exists, and novel drugs are needed to either delay the onset of ARDS or reduce its severity in this cohort of influenza-infected patients. Such drugs could reduce the potential for ICU overload in pandemic situations (29,30), maintaining the ability of the healthcare system to provide adequate care to all who require it (12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Future analysis may help to refine this threshold and thus may have to take into account how long it is exceeded. The magnitude of a pandemic and its consequences on the organization of a health-care system depend on several parameters and are notoriously difficult to predict [21,22]. Therefore, experiences reported during the first waves throughout the world were useful to better elaborate forecasts taking into account different attack rates and epidemic wave durations [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric caregivers in Canada were often overworked as admissions rose. After the experience in Manitoba, Canada, where ICUs were nearly overwhelmed with critically ill patients during the first wave of the pandemic, a stockpile of ventilators was increased in some jurisdictions in order to help face such a sudden increase in critically ill patients in other areas [50,101]. In order to estimate the risk of mismatch between demand and capacity of PICUs, a modeling exercise was performed with different attack rates.…”
Section: Disease Burden On Healthcare Resourcesmentioning
confidence: 99%
“…Some studies performed using data from the first wave suggested a possible mismatch between resources (e.g., ventilators and PICU beds) and care demands [50,51]. To improve forecasting, it will be necessary to improve real-time data collection and further delineate geography-and population-specific risks.…”
Section: Adaptation Of Health Resources To Pandemic Burdenmentioning
confidence: 99%